The Communication Crisis of Restoring the Reputation of Indonesian National Police Post the Murder of Brigadier Josua on Online Media. - Nurhakki, Nurhakki; Hayana, Hayana; Waliyuddin, Waliyuddin (Palakka : Media and Islamic Communication, 2023)
Crisis communication is a strategy for managing crisis situations through the process of sending and receiving information during or after a crisis event with the aim of managing the situation, minimizing damage, and ensuring the safety of the people involved, or victims. The leadership of the National Police institution has an important role in carrying out crisis communications as a communicator in improving the organization's reputation. The scandal, which was not carried out institutionally, but involved the involvement of high-ranking police officials and a number of other police officers, caused the reputation of the police organization to experience the threat of a crisis of public distrust. Law enforcement agencies that are actually faced with violations of the law are demanded by both the families of victims and the public that police agencies prioritize transparency, accountability and justice in resolving cases. The three stages of the press conference as a form of conveying the National Police Chief's crisis communication were chosen for analysis, namely the press conference held on August 4, 9 and 25 2022. Based on the content analysis, it was concluded that the most highlighted messages were relevant messages, messages emphasizing credibility, and statements. ongoing process. Meanwhile, the Timely message and messages of empathy for victims were not highlighted in the National Police Chief's press conference to show that empathy is an important thing in the National Police Chief's crisis message.